Fault-Tolerant Data Aggregation Scheme Supporting Fine-Grained Linear Operation in Smart Grid - Zichao Song; Tanping Zhou; Weidong Zhong; Dong Chen; Longfei Liu; Xiaoyuan Yang (IEEE Access, 2023)
Smart grid is a combination of traditional power system engineering and information and communication technology. Smart grid provides users with convenient services through real-time data updates. Multi-dimensional data aggregation can be more flexible for statistical analysis of electricity information. However, most of the existing multi-dimensional data aggregation schemes require the participation of a trusted third party and do not support fault tolerance. In this paper, we propose a fault-tolerant data aggregation scheme supporting fine-grained linear operations in smart grid. Firstly, we used the Chinese remainder theorem to encode the user’s multi-dimensional data and the corresponding weights. Secondly, we construct a privacy-preserving data aggregation scheme without a trusted third party, by combining paillier homomorphic encryption scheme and a secure key agreement protocol. Finally, we use the extended Shamir secret sharing scheme to construct a fault-tolerant data aggregation scheme that supports the reuse of shared key shares. Security analysis results show that our scheme satisfies semantic security and user data privacy protection. Experimental results show that compared with the existing multidimensional data aggregation schemes that require a trusted third party, our scheme does not increase additional computation and communication overhead.